Combined effect of the QBO and ENSO on the MJO - Liying SUN; Hui WANG; Fei LIU (Atmospheric and Oceanic Science Letters, 2019)
This study investigates the combined effect of the El Niño–Southern Oscillation (ENSO) and stratospheric quasi-biennial oscillation (QBO) on the Madden Julian Oscillation (MJO). The results show that the western Pacific MJO originating from the Indian Ocean during La Niña/QBO easterly years is stronger than that during El Niño years. This relation, however, disappears during La Niña/QBO westerly years. The reason is that ENSO and the QBO have different effects on each MJO event. For an El Niño year, there is only about one MJO event, and the QBO effect is small. During a La Niña/QBO easterly year, there are 1.7 MJO events, while during a La Niña/QBO westerly year, there are only 0.6 MJO events. El Niño can reinforce the MJO over the western Pacific because of the positive moisture advection of the El Niño mean state by MJO easterly wind anomalies. The QBO mainly affects the MJO over the Maritime Continent region by changing the high-cloud-controlled diurnal cycle; and the Maritime Continent barrier effect is enhanced during the QBO westerly phase because of the strong diurnal cycle. During El Niño years, even the MJO over the Maritime Continent is suppressed by the QBO westerly phase; the MJO can be reinforced over the western Pacific. During La Niña/QBO westerly years, the MJO over the Maritime Continent is suppressed because of the strong Maritime Continent diurnal cycle, and it is further suppressed over the western Pacific because of the lack of a reinforcement process.